Diversity of trion states and substrate effects in the optical properties of an MoS2 monolayer - Matthias Drüppel (Nature Portfolio, 2017)
The optical and electrical properties of atomically thin transition metal dichalcogenides critically depend on the underlying substrate. Here, the authors develop an abinitio many-body formalism to investigate the full spectrum of negative and positive trions in these layered semicondutors.